PROSES PEMBUATAN PULP BERBASIS AMPAS TEBU: BATANG PISANG DENGAN METODE ACETOSOLVE - Zulferiyenni Zulferiyenni; Otik Nawansih; Sri Hidayati (Jurnal Teknologi & Industri Hasil Pertanian, 2009)
In Indonesia, pulp and paper production generally uses wood.  Intensive forest explotation causes deforesting, global warming,and lessen the wood deposit and forest area.  Therefore, government should seek alternative raw material such as bagasse for pulp and paper production, with naturally friendly environment pulping method, such as acetosolve method. In this research bagasse and banana fiber were used as raw material for pulp production.  Then, raw material analyses was conducted for chemical content which were cellulose, hemicellulose, lignin, and ash, and  pulp physical properties.  The best result in pulping process was 70:30 ratio of bagasse and banana fiber with 80% acetate acid concentration which resulted 56% of cellulose, 27,4% of hemicellulose, 16,2% of lignin, 66% rendemen, 16.1 GE of brightness index,  0,83 (kPa.m/g) of  break index, 2,05 Nm2/Kg Of tear index,  19 Nm/g of tensil strength, and 93% of paper opacity. Keywords: Bagasse, banana trunk fiber, acetosolve